Morphological features of mice of the genus Sylvaemus under conditions of syntopy in the eastern forest steppe of Ukraine - Oksana Markovska (Theriologia Ukrainica, 2023)
The opinion regarding morphological changes in S. sylvaticus depending on being in syntopy with the competing sibling species S. tauricus is ambiguous. Most authors claim that allotopic and syntopic populations do not differ. Some of them indicate a tendency that the size of S. sylvaticus increases in allotopic populations, while others claim that such increase occurs in syntopic populations. There is an assumption that the nature of morphological changes in S. sylvaticus undergoes geographic variability and manifests differently in different parts of the range. Overall, the authors suggest that character change is an adaptive response of a subordinate species to the presence of a dominant competitor, so character change as a result of competitive interaction is more likely to occur in S. sylvaticus than in S. tauricus. The research was conducted in the territory of Kharkiv Oblast, Ukraine. During the observation period, from spring 2017 to autumn 2022, 666 specimens of the genus Sylvaemus were caught in 10 selected biotopes. Different types of oak forests, dry and floodplain meadows, riparian vegetation, steppe areas, chalk slopes, field protection forest strips, fields, as well as various ecotones were studied. According to the results of the research, being in syntopy with S. tauricus, S. sylvaticus has statistically significantly higher average values of parameters of exterior characters, which largely complicates the identification of these two species in the field. For the most part, confusion in identification occurs in forest biotopes, namely in dry and fresh maple–linden forests. Only two species are found in the studied oak forests in the territory of Kharkiv Oblast—S. sylvaticus and S. tauricus, whereas S. uralensis occurs only on forest edges. And it is in the oak forests that large specimens of S. sylvaticus are found, which in habitus closely resemble S. tauricus. In open biotopes, S. sylvaticus is closer in size to S. uralensis, often young or moulting individuals are very similar even in fur colour. Individuals of S. sylvaticus with a weakly expressed chest spot, and sometimes barely noticeable, are found in the steppe areas of Kharkiv Oblast. No differences in external characters were found in mice of the genus Sylvaemus that inhabit different biotopes, the morphospaces of the samples overlapped in all three species.